Full counting statistics of superconductor hybrid structures involving a time-dependent field - Soller, Henning; Dajani, Saleem al (Physics letters, 2024)
Here we discuss the charge transfer statistics of superconductor-quantum dot-superconductor contacts in nonequilibrium and involving a time-dependent field via the applied voltage. In this case, the effects of multiple Andreev reflections and the Josephson effect exhibit distinctive features. In addition to the effects observable in the conductance, we will also discuss the effects observable in the noise.
Online veröffentlicht: 13. August 2024
Gesehen am 18.03.2025